Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fpsyg.2021.689396
|View full text |Cite
|
Sign up to set email alerts
|

Life With Corona: Increased Gender Differences in Aggression and Depression Symptoms Due to the COVID-19 Pandemic Burden in Germany

Abstract: Gender differences (GD) in mental health have come under renewed scrutiny during the COVID-19 pandemic. While rapidly emerging evidence indicates a deterioration of mental health in general, it remains unknown whether the pandemic will have an impact on GD in mental health. To this end, we investigate the association of the pandemic and its countermeasures affecting everyday life, labor, and households with changes in GD in aggression, anxiety, depression, and the somatic symptom burden. We analyze cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 191 publications
0
13
1
1
Order By: Relevance
“…During the COVID-19 pandemic, this gender difference even exacerbated ( Covid-19 Mental Disorders Collaborators, 2021 ). Women were shown to have higher levels of anxiety and depression ( Benke et al, 2020 ; Abreu et al, 2021 ; Ferreira et al, 2021 ) and a lower quality of life ( Teotônio et al, 2020 ; Ferreira et al, 2021 ) compared to men during the pandemic. In line with these results, our data show enhanced risk for a decreased general health status, and furthermore enhanced risk for a decrease of quality of life and relationship with their partner compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, this gender difference even exacerbated ( Covid-19 Mental Disorders Collaborators, 2021 ). Women were shown to have higher levels of anxiety and depression ( Benke et al, 2020 ; Abreu et al, 2021 ; Ferreira et al, 2021 ) and a lower quality of life ( Teotônio et al, 2020 ; Ferreira et al, 2021 ) compared to men during the pandemic. In line with these results, our data show enhanced risk for a decreased general health status, and furthermore enhanced risk for a decrease of quality of life and relationship with their partner compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…Special attention should be drawn towards groups of people that might be more prone to such adverse consequences. As such, studies have shown that certain groups of people have higher risks for depression, anxiety, and lower quality of life during the pandemic, as seen in women [ 9 , 12 , 15 , 16 , 17 ], younger people [ 9 , 12 , 15 ], people with financial strain [ 18 , 19 ], the unemployed [ 9 , 15 ], and those with previously existing mental health or physical health conditions [ 12 , 17 , 20 ]. On the other hand, several protective factors were also identified to be unequally distributed in the population, encompassing, among others, living with a partner [ 9 , 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The closure of education centres and nursery schools led to an increase in children’s care and the volume of household chores. This situation may have contributed to more significant differences between women and men during the lockdown in different communities (18,6569).…”
Section: Discussionmentioning
confidence: 99%